Macroscopic observations on the long‐term effects of cathodic protection applied to carbonated reinforced concrete. Issue 8 (28th August 2014) - Redaelli, E.; Bertolini, L.
<x xml:space="preserve">Abstract</x> The aim of the paper was to study macroscopic long‐term modifications induced by cathodic protection (CP) applied to carbonated concrete, in order to localise possible deterioration phenomena that can affect the performance of the protection system. Carbonated reinforced specimens that had been subjected to CP for 13 years were analysed with phenolphthalein indicator, that allowed to highlight a pH reduction in the originally alkaline mortar in which the anode was embedded. The pH reduction was localised in the mortar in contact with carbonated concrete, rather than directly in contact with the anode. The thickness of the layer with reduced pH increased with the circulated charge and was nil on specimens that were not subjected to current application. This modification was attributed to a mechanism of dissolution of calcium hydroxide in the mortar. Although a thorough qualitative and quantitative description of the modifications requires further investigations, the results provide a better understanding of possible deterioration phenomena at the anode and they indicate that such phenomena may be hindered by embedding the anode mesh in an adequate layer of alkaline mortar and keeping the current at the least value that is necessary to protect the steel from corrosion.